A perovskite solar cell buried bottom interface layer based on 3-aminopropyl hydrogen iodate phosphate and 1,4-benzene diphosphonic acid synergistic passivation and a preparation method thereof
Patent Information
- Application Number
- CN202610978888.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-02
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本发明的目的是克服现有技术中单一分子策略功能不足的问题,旨在空穴传输层(如NiOx、PTAA或SAM)表面引入由3-氨基丙基磷酸氢碘酸盐和1,4-苯二膦酸组成的协同钝化层,通过3-氨基丙基磷酸氢碘酸盐和1,4-苯二膦酸的协同效应,解决现有技术中钙钛矿薄膜埋底界面缺陷多、结晶质量差、应力大以及器件性能不足的问题
[0038]本发明通过3-氨基丙基磷酸氢碘酸盐与1,4-苯二膦酸的协同作用,在空穴传输层与钙钛矿间构建了强效的化学锚定与缺陷钝化双功能界面。1,4-苯二膦酸利用双膦酸基团与底部传输层形成稳固共价键,增强层间附着力,而3-氨基丙基磷酸氢碘酸盐则通过多位点配位精准修复钙钛矿底部的负电荷缺陷。两者的组合不仅显著降低了界面处的非辐射复合损失,提升了开路电压与电荷提取速率,还改善了界面浸润性,诱导大晶粒钙钛矿生长。这使得器件在大幅提升光电转换效率的同时,显著抑制了离子迁移与迟滞现象,并展现出优异的大面积加工适配性。
Smart Images

Figure CN122995408A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of novel photovoltaic technology, specifically relating to a synergistic modification method for the buried interface layer of perovskite solar cells. By leveraging the synergistic effect of organic ammonium salt (3-aminopropyl phosphate diiodate) and aromatic phosphonic acid molecules (1,4-phenylenediamine), the limitations of existing single passivator strategies are overcome, thereby improving cell efficiency. Background Technology
[0002] In the field of novel thin-film photovoltaic technology, perovskite solar cells have become one of the most promising next-generation photovoltaic technologies due to their superior photoelectric properties, such as high absorption coefficient, long carrier diffusion length, and tunable bandgap. In a typical device structure, the hole transport layer, as a key functional layer supporting the growth of the perovskite thin film and responsible for charge extraction, plays a crucial role in the final photoelectric conversion efficiency of the device through the "buried interface" formed between it and the perovskite active layer. Due to issues such as energy level mismatch and wettability differences in the hole transport layer, a large number of uncoordinated lead ions and micropores are easily generated at the interface during the nucleation and growth of the perovskite. These defects at the buried interface trap carriers and induce severe nonradiative recombination, resulting in significant losses in the open-circuit voltage and fill factor of the device.
[0003] Furthermore, uncoordinated lead ions and halogen vacancies at the buried interface readily become channels for ion migration, inducing component decomposition under illumination, heat, or electric fields, leading to rapid degradation of device performance. Traditional interface modification typically employs single-functional passivation molecules, but a single molecule often struggles to simultaneously achieve strong anchoring of the hole transport layer surface, deep repair of perovskite layer defects, and effective control of interface energy levels. For example, while some organic salt passivators can repair A-vacancy defects through electrostatic interactions, their effect on other deep-level defects is limited; and while certain aromatic phosphonic acid molecules can coordinate with uncoordinated lead and improve wettability, their single phosphonic acid functional groups are insufficient to completely cover subtle interface defects. Therefore, designing a multifunctional molecular combination with synergistic effects to construct a buried interface layer between the hole transport layer and the perovskite layer that enhances chemical bonding anchoring, performs multi-site defect passivation, and optimizes charge extraction kinetics is a key technical challenge for improving the performance of perovskite solar cells. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of single-molecule strategies in existing technologies, and to address the issue of insufficient functionality in hole transport layers (such as NiO). xA synergistic passivation layer composed of 3-aminopropyl hydroiodide phosphate and 1,4-benzenediphosphonic acid is introduced onto the surface of perovskite films (PTAA or SAM). Through the synergistic effect of 3-aminopropyl hydroiodide phosphate and 1,4-benzenediphosphonic acid, the problems of numerous buried interface defects, poor crystal quality, high stress, and insufficient device performance in existing technologies are solved.
[0005] Based on the above technical concept, this invention constructs a composite interface layer with "strong anchoring and multi-point passivation" characteristics at the buried interface through the intermolecular synergistic effect of 3-aminopropyl phosphate diiodate and 1,4-phenylenediamine. Specifically, 1,4-phenylenediamine utilizes the rigidity of its aromatic ring structure and the strong coordination ability of its bisphosphonate groups to form a stable covalent bond or strong chemical interaction with the surface of the bottom hole transport layer, thereby constructing a dense molecular substrate film. At the other end, it interacts with uncoordinated lead in the perovskite. 3-aminopropyl phosphate diiodate, as a functional salt, contains positively charged amino groups that can effectively passivate negatively charged defects at the buried interface. The synergistic effect of these two molecules provides nucleation sites for the crystallization of the perovskite film and plays a role in regulating nucleation kinetics in the early stages of perovskite film growth, assisting perovskite crystallization and improving film quality. The synergistic effect not only achieves bidirectional defect repair from the bottom transport layer to the top perovskite layer but also significantly reduces non-radiative recombination loss at the buried interface, accelerating hole extraction and transport. In addition, the composite passivation layer improves the wettability of the hole transport layer surface, enabling it to exhibit excellent film uniformity in large-area fabrication processes (such as slot coating), thereby improving the photoelectric conversion efficiency of the device and significantly enhancing the operational stability of the battery under long-term humid and hot conditions.
[0006] The technical solution of this invention is:
[0007] In a first aspect, the present invention provides a buried interface passivation layer for perovskite solar cells based on the synergistic passivation of 3-aminopropylphosphonic acid hydroiodate and 1,4-phenylbisphosphonic acid, wherein the passivation materials of the buried interface passivation layer are 3-aminopropylphosphonic acid hydroiodate and 1,4-phenylbisphosphonic acid, and the structural formula is shown below:
[0008] a) 3-Aminopropylphosphonate hydroiodide
[0009]
[0010] b) 1,4-Benzodiphosphonic acid
[0011]
[0012] The ratio of 3-aminopropyl phosphate hydroiodate to 1,4-benzenediphosphonic acid is x:1-x, where 0≤x≤1.
[0013] Secondly, the present invention provides a method for preparing a buried interface passivation layer for perovskite solar cells based on the synergistic passivation of 3-aminopropyl hydroiodide phosphate and 1,4-phenyldiphosphonic acid. The method involves dissolving 3-aminopropyl hydroiodide phosphate and 1,4-phenyldiphosphonic acid in solvents to obtain precursor solutions; mixing the obtained precursor solutions to obtain a buried interface passivation solution; and depositing the obtained buried interface passivation solution onto a hole transport layer.
[0014] The precursor solution concentration is 0.01 mg / mL-1.0 mg / mL, and the solvent is isopropanol or ethanol;
[0015] The ratio of 3-aminopropyl phosphate hydroiodate to 1,4-benzenediphosphonic acid is x:1-x, 0≤x≤1.
[0016] Thirdly, the present invention provides a perovskite solar cell based on the synergistic passivation of the buried interface by 3-aminopropyl phosphate diiodate and 1,4-phenylenediamine, which is a PIN structure and includes, from bottom to top, a transparent conductive substrate, a hole transport layer, a buried interface passivation layer, a perovskite, an electron transport layer, a buffer layer and an electrode, wherein the buried interface passivation layer is the buried interface passivation layer of the perovskite solar cell based on the synergistic passivation of 3-aminopropyl phosphate diiodate and 1,4-phenylenediamine as described in the first aspect of the present invention.
[0017] Furthermore, this invention provides a method for preparing perovskite solar cells based on the synergistic passivation of the buried interface by 3-aminopropyl phosphate diiodate and 1,4-phenylbisphosphonic acid, the method comprising:
[0018] (1) Obtain a substrate, spin-coat a hole transport layer solution onto the substrate, and anneal to prepare a hole transport layer;
[0019] (2) A mixed solution of 3-aminopropyl phosphate hydroiodate and 1,4-benzenediphosphonic acid was deposited on the hole transport layer to obtain a buried interface passivation layer.
[0020] (3) The perovskite precursor solution was coated on the passivation layer of the buried interface and annealed to prepare the perovskite light-absorbing layer.
[0021] (4) Electron transport layer precursor material is deposited on the surface of perovskite light-absorbing layer to prepare electron transport layer;
[0022] (5) A buffer layer is prepared by spin-coating on the electron transport layer;
[0023] (6) Prepare metal electrodes on the buffer layer.
[0024] The substrate mentioned in step (1) is any one of ITO conductive glass, transparent conductive flexible plastic, crystalline silicon substrate, conductive flexible stainless steel, and copper indium gallium selenide substrate;
[0025] The hole transport layer mentioned in step (1) is SAMs, NiO X PTAA, P3CT, or any one or more materials; spin coating speed is 1000 ~ 5000 rpm / min, time is 20 ~ 40 s; annealing conditions are: annealing in ambient air at 100 ~ 150℃ for 10 ~ 30 min;
[0026] The solvent for the mixed solution of 3-aminopropyl phosphate diiodide and 1,4-benzenediphosphonic acid in step (2) is any one or more mixed solutions of isopropanol, ethanol, methanol, etc., with a concentration of 0.01 ~ 1.0 mg / mL; the concentration ratio of 3-aminopropyl phosphate diiodide and 1,4-benzenediphosphonic acid is 1:1-x, 0≤x≤1; the spin coating speed is 1000 ~ 5000 rpm / min, the time is 20 ~ 40 s; the annealing temperature is 50 ~ 150℃, and the annealing time is 1 ~ 10 min;
[0027] The perovskite precursor solution in step (3) is a mixture of any one or more of dimethylformamide, dimethyl sulfoxide, γ-butyrolactone, and N-methylpyrrolidone, with the solute being ABX3 type perovskite, where 0 ≤ x ≤ 3; and the A-site is methylamine (MA). + ), formamidin (FA) + ), Cs + and its mixed cations, with Pb at the B site. 2+ Sn 2+ and its mixed cations, with Cl at the X position. - ,Br - I - and its mixed anions; the concentration of the solute is 1.0 ~ 1.6 mol / L;
[0028] The perovskite light-absorbing layer in step (3) is prepared by annealing after solution coating or slit coating of perovskite precursor. The coating speed is 9 mm / s and the coating speed of slit coating is 15 mm / s. The annealing conditions are: annealing at 100-140℃ in ambient air for 20-30 min. The thickness of the perovskite light-absorbing layer is 200-1000 nm.
[0029] The electron transport layer mentioned in step (4) is PC 61 BM, C 60 Any one or two materials; spin coating speed of 1000~5000 rpm / min, time of 20~40 s;
[0030] The buffer layer mentioned in step (5) is BCP, the spin coating speed is 3000 ~ 6000 rpm / min, and the time is 20 ~ 40s;
[0031] The metal electrode mentioned in step (6) is any one of silver, gold, or copper, deposited at 60-100 nm by vacuum evaporation.
[0032] This invention further provides an application of a buried interface layer for perovskite solar cells based on the synergistic passivation of the buried interface by 3-aminopropyl diiodophosphate and 1,4-phenylbisphosphonic acid, suitable for perovskite-based tandem solar cells, including at least the following structural devices:
[0033] e) Perovskite / perovskite tandem solar cells;
[0034] f) Perovskite / crystalline silicon tandem solar cells;
[0035] g) Perovskite / organic tandem solar cells;
[0036] h) Perovskite / copper indium gallium selenide tandem solar cell.
[0037] The technical effects of this invention are:
[0038] This invention utilizes the synergistic effect of 3-aminopropyl diiodophosphate and 1,4-phenylenediamine to construct a highly effective dual-functional interface for chemical anchoring and defect passivation between the hole transport layer and the perovskite. 1,4-phenylenediamine forms a stable covalent bond with the bottom transport layer using its bisphosphonic group, enhancing interlayer adhesion, while 3-aminopropyl diiodophosphate precisely repairs the negative charge defects at the bottom of the perovskite through multi-site coordination. This combination significantly reduces non-radiative recombination losses at the interface, improves open-circuit voltage and charge extraction rate, and enhances interface wettability, inducing the growth of large-grain perovskite. This results in a device that significantly improves photoelectric conversion efficiency while significantly suppressing ion migration and hysteresis, and exhibits excellent large-area fabrication adaptability. Attached Figure Description
[0039] Figure 1 This is a schematic diagram of the perovskite solar cell structure provided by the present invention;
[0040] Figure 2 This is the current-voltage characteristic curve of the battery obtained by modifying the buried interface with a mixed solution of 3-aminopropyl phosphate hydroiodate solution: 1,4-benzenediphosphonic acid solution: ethanol in a volume ratio of 0.5:0.5:9, as provided in Example 1 of this invention.
[0041] Figure 3 This is the current-voltage characteristic curve of the battery obtained by modifying the buried interface with a mixed solution of 3-aminopropyl phosphate hydroiodate solution, 1,4-benzenediphosphonic acid solution and ethanol in a volume ratio of 1:1:8, as provided in Example 2 of the present invention.
[0042] Figure 4 This is the current-voltage characteristic curve of the battery obtained by modifying the buried interface with a mixed solution of 3-aminopropyl phosphate hydroiodate solution: 1,4-benzenediphosphonic acid solution: ethanol in a volume ratio of 2:2:6, as provided in Example 3 of the present invention.
[0043] Figure 5 This is the current-voltage characteristic curve of the battery obtained by modifying the buried interface with a mixed solution of 3-aminopropyl phosphate hydroiodate solution, 1,4-benzenediphosphonic acid solution and ethanol in a volume ratio of 1:0:9, as provided in Example 4 of the present invention.
[0044] Figure 6 This is the current-voltage characteristic curve of the battery obtained by modifying the buried interface with a mixed solution of 3-aminopropyl phosphate hydroiodate solution: 1,4-benzenediphosphonic acid solution: ethanol in a volume ratio of 0:1:9, as provided in Example 5 of the present invention.
[0045] Figure 7 This is a graph showing the current-voltage characteristics of the battery obtained from the unmixed solution-modified buried interface provided in Comparative Example 1 of this invention. Detailed Implementation
[0046] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0047] This invention provides a method for fabricating perovskite solar cells based on the synergistic passivation of the buried interface using 3-aminopropyl diiodophosphate and 1,4-phenylenediamine. The method utilizes passivating molecules to modify and optimize the buried interface of the perovskite film, improving the connection between the substrate and the perovskite. See [link to documentation]. Figure 1 The battery structure is stacked from bottom to top as a substrate, a hole transport layer, a buried interface passivation layer, a perovskite light-absorbing layer, an electron transport layer, and a metal electrode.
[0048] Example 1
[0049] This invention provides a method for preparing a perovskite solar cell based on the synergistic passivation of the buried interface by 3-aminopropyl phosphate diiodate and 1,4-phenylbisphosphonic acid, comprising the following steps:
[0050] 1. Place an ITO conductive glass substrate (2 × 2 cm) 2 The substrate was ultrasonically cleaned sequentially with detergent, deionized water and isopropanol for 30 min, dried with nitrogen, and treated with ultraviolet ozone for 20 min to obtain a clean and well wettable ITO conductive glass substrate.
[0051] 2. Add 20 mg NiO X NiO was prepared by dissolving the powder in 1 mL of deionized water. X Hole transport layer solution;
[0052] 3. Take the NiO from step 2 X The hole transport layer solution was spin-coated onto the ITO conductive glass substrate of step 1 at a speed of 2000 rpm / min for 30 s; then, it was annealed in ambient air at 130°C for 20 min; thus, the hole transport layer was prepared.
[0053] 4. Dissolve 0.5 mg of 3-aminopropyl phosphate diiodate in 1 mL of ethanol to obtain a 3-aminopropyl phosphate diiodate precursor solution. Dissolve 0.5 mg of 1,4-phenyldiphosphonic acid in 1 mL of ethanol to obtain a 1,4-phenyldiphosphonic acid precursor solution. Mix the 3-aminopropyl phosphate diiodate precursor solution, 1,4-phenyldiphosphonic acid precursor solution, and ethanol in a volume ratio of 0.5:0.5:9 to obtain a solution for passivating the buried interface.
[0054] 5. Take the passivation solution obtained in step 4 and spin-coat it onto the hole transport layer obtained in step 3. The spin-coating speed is 4000 rpm / min and the spin-coating time is 30 s. Then anneal it at 100℃ for 10 min in a nitrogen atmosphere.
[0055] 6. Dissolve 571.65 mg lead iodide, 215.89 mg lead bromide, 13.35 mg lead chloride, 215.89 mg formamidinium hydroiodide, 91.45 mg cesium iodide and 14.04 mg methylammonium hydrochloride in a mixed solution of dimethylformamide and N-methylpyrrolidone in a volume ratio of 800 μL:200 μL. Stir under nitrogen atmosphere until completely dissolved to obtain perovskite precursor solution;
[0056] 7. Take the perovskite solution obtained in step 6 and coat it onto the buried interface layer obtained in step 5. The coating speed is 9 mm / s and the blade spacing is 200 μm. Dry the film by nitrogen extraction. Then anneal it in nitrogen at 130 °C for 30 min. A perovskite light-absorbing layer with a thickness of about 600 nm is prepared.
[0057] 8. Take 20 mg PC 61 BM was dissolved in 1 mL of chlorobenzene and stirred until completely dissolved to obtain PC. 61 BM solution: Dissolve 0.5 mg BCP in 1 mL isopropanol and stir until completely dissolved to obtain a buffer solution;
[0058] 9. The solution obtained in step 8 is spin-coated onto the perovskite light-absorbing layer obtained in step 7 using a spin-coating method. 61 The spin coating speed of BM was 2000 rpm / min and the spin coating time was 30 s. The spin coating speed of BCP was 5000 rpm / min and the spin coating time was 30 s to prepare the electron transport layer.
[0059] 10. A silver film with a thickness of 80 nm is deposited on the thin film obtained in step 9 to obtain a perovskite solar cell.
[0060] Experimental Results: Performance testing of solar cells was conducted, such as... Figure 2 As shown, at AM1.5, 100 mW / cm 2 Under standard light intensity irradiation, the solar cell prepared in this embodiment exhibits an open-circuit voltage of 1.232 V and a short-circuit current density of 20.80 mA / cm². 2 The fill factor is 83.31%, and the efficiency is 21.37%.
[0061] Example 2
[0062] This invention provides a method for preparing a perovskite solar cell based on the synergistic passivation of the buried interface by 3-aminopropyl phosphate diiodate and 1,4-phenylbisphosphonic acid, comprising the following steps:
[0063] 1. Place an ITO conductive glass substrate (2 × 2 cm) 2 The substrate was ultrasonically cleaned sequentially with detergent, deionized water and isopropanol for 30 min, dried with nitrogen, and treated with ultraviolet ozone for 20 min to obtain a clean and well wettable ITO conductive glass substrate.
[0064] 2. Add 20 mg NiO X NiO was prepared by dissolving the powder in 1 mL of deionized water. X Hole transport layer solution;
[0065] 3. Take the NiO from step 2 X The hole transport layer solution was spin-coated onto the ITO conductive glass substrate of step 1 at a speed of 2000 rpm / min for 30 s; then, it was annealed in ambient air at 130°C for 20 min; thus, the hole transport layer was prepared.
[0066] 4. Dissolve 0.5 mg of 3-aminopropyl phosphate diiodate in 1 mL of ethanol to obtain a 3-aminopropyl phosphate diiodate precursor solution. Dissolve 0.5 mg of 1,4-phenyldiphosphonic acid in 1 mL of ethanol to obtain a 1,4-phenyldiphosphonic acid precursor solution. Mix the 3-aminopropyl phosphate diiodate precursor solution, 1,4-phenyldiphosphonic acid precursor solution, and ethanol in a volume ratio of 1:1:8 to obtain a solution for passivating the buried interface.
[0067] 5. Take the passivation solution obtained in step 4 and spin-coat it onto the hole transport layer obtained in step 3. The spin-coating speed is 4000 rpm / min and the spin-coating time is 30 s. Then anneal it at 100℃ for 10 min in a nitrogen atmosphere.
[0068] 6. Dissolve 571.65 mg lead iodide, 215.89 mg lead bromide, 13.35 mg lead chloride, 215.89 mg formamidinium hydroiodide, 91.45 mg cesium iodide and 14.04 mg methylammonium hydrochloride in a mixed solution of dimethylformamide and N-methylpyrrolidone in a volume ratio of 800 μL:200 μL. Stir under nitrogen atmosphere until completely dissolved to obtain perovskite precursor solution;
[0069] 7. Take the perovskite solution obtained in step 6 and coat it onto the buried interface layer obtained in step 5. The coating speed is 9 mm / s and the blade spacing is 200 μm. Dry the film by nitrogen extraction. Then anneal it in nitrogen at 130 °C for 30 min. A perovskite light-absorbing layer with a thickness of about 600 nm is prepared.
[0070] 8. Take 20 mg PC 61 BM was dissolved in 1 mL of chlorobenzene and stirred until completely dissolved to obtain PC. 61 BM solution: Dissolve 0.5 mg BCP in 1 mL isopropanol and stir until completely dissolved to obtain a buffer solution;
[0071] 9. The solution obtained in step 8 is spin-coated onto the perovskite light-absorbing layer obtained in step 7 using a spin-coating method. 61 The spin coating speed of BM was 2000 rpm / min and the spin coating time was 30 s. The spin coating speed of BCP was 5000 rpm / min and the spin coating time was 30 s to prepare the electron transport layer.
[0072] 10. A silver film with a thickness of 80 nm is deposited on the thin film obtained in step 9 to obtain a perovskite solar cell.
[0073] Experimental Results: Performance testing of solar cells was conducted, such as... Figure 3 As shown, at AM1.5, 100 mW / cm 2 Under standard light intensity irradiation, the solar cell prepared in this embodiment exhibits an open-circuit voltage of 1.243 V and a short-circuit current density of 21.31 mA / cm². 2 The fill factor is 84.45%, and the efficiency is 22.39%.
[0074] Example 3
[0075] This invention provides a method for preparing a perovskite solar cell based on the synergistic passivation of the buried interface by 3-aminopropyl phosphate diiodate and 1,4-phenylbisphosphonic acid, comprising the following steps:
[0076] 1. Place an ITO conductive glass substrate (2 × 2 cm) 2The substrate was ultrasonically cleaned sequentially with detergent, deionized water and isopropanol for 30 min, dried with nitrogen, and treated with ultraviolet ozone for 20 min to obtain a clean and well wettable ITO conductive glass substrate.
[0077] 2. Add 20 mg NiO X NiO was prepared by dissolving the powder in 1 mL of deionized water. X Hole transport layer solution;
[0078] 3. Take the NiO from step 2 X The hole transport layer solution was spin-coated onto the ITO conductive glass substrate of step 1 at a speed of 2000 rpm / min for 30 s; then, it was annealed in ambient air at 130°C for 20 min; thus, the hole transport layer was prepared.
[0079] 4. Dissolve 0.5 mg of 3-aminopropyl phosphate diiodate in 1 mL of ethanol to obtain a 3-aminopropyl phosphate diiodate precursor solution. Dissolve 0.5 mg of 1,4-phenyldiphosphonic acid in 1 mL of ethanol to obtain a 1,4-phenyldiphosphonic acid precursor solution. Mix the 3-aminopropyl phosphate diiodate precursor solution, 1,4-phenyldiphosphonic acid precursor solution, and ethanol in a volume ratio of 2:2:6 to obtain a solution for passivating the buried interface.
[0080] 5. Take the passivation solution obtained in step 4 and spin-coat it onto the hole transport layer obtained in step 3. The spin-coating speed is 4000 rpm / min and the spin-coating time is 30 s. Then anneal it at 100℃ for 10 min in a nitrogen atmosphere.
[0081] 6. Dissolve 571.65 mg lead iodide, 215.89 mg lead bromide, 13.35 mg lead chloride, 215.89 mg formamidinium hydroiodide, 91.45 mg cesium iodide and 14.04 mg methylammonium hydrochloride in a mixed solution of dimethylformamide and N-methylpyrrolidone in a volume ratio of 800 μL:200 μL. Stir under nitrogen atmosphere until completely dissolved to obtain perovskite precursor solution;
[0082] 7. Take the perovskite solution obtained in step 6 and coat it onto the buried interface layer obtained in step 5. The coating speed is 9 mm / s and the blade spacing is 200 μm. Dry the film by nitrogen extraction. Then anneal it in nitrogen at 130 °C for 30 min. A perovskite light-absorbing layer with a thickness of about 600 nm is prepared.
[0083] 8. Take 20 mg PC 61 BM was dissolved in 1 mL of chlorobenzene and stirred until completely dissolved to obtain PC. 61BM solution: Dissolve 0.5 mg BCP in 1 mL isopropanol and stir until completely dissolved to obtain a buffer solution;
[0084] 9. The solution obtained in step 8 is spin-coated onto the perovskite light-absorbing layer obtained in step 7 using a spin-coating method. 61 The spin coating speed of BM was 2000 rpm / min and the spin coating time was 30 s. The spin coating speed of BCP was 5000 rpm / min and the spin coating time was 30 s to prepare the electron transport layer.
[0085] 10. A silver film with a thickness of 80 nm is deposited on the thin film obtained in step 9 to obtain a perovskite solar cell.
[0086] Experimental Results: Performance testing of solar cells was conducted, such as... Figure 4 As shown, at AM1.5, 100 mW / cm 2 Under standard light intensity irradiation, the solar cell prepared in this embodiment exhibits an open-circuit voltage of 1.232 V and a short-circuit current density of 20.81 mA / cm². 2 The fill factor is 83.21%, and the efficiency is 21.37%.
[0087] Example 4
[0088] This invention provides a method for preparing a perovskite solar cell based on the synergistic passivation of the buried interface by 3-aminopropyl phosphate diiodate and 1,4-phenylbisphosphonic acid, comprising the following steps:
[0089] 1. Place an ITO conductive glass substrate (2 × 2 cm) 2 The substrate was ultrasonically cleaned sequentially with detergent, deionized water and isopropanol for 30 min, dried with nitrogen, and treated with ultraviolet ozone for 20 min to obtain a clean and well wettable ITO conductive glass substrate.
[0090] 2. Add 20 mg NiO X NiO was prepared by dissolving the powder in 1 mL of deionized water. X Hole transport layer solution;
[0091] 3. Take the NiO from step 2 X The hole transport layer solution was spin-coated onto the ITO conductive glass substrate of step 1 at a speed of 2000 rpm / min for 30 s; then, it was annealed in ambient air at 130°C for 20 min; thus, the hole transport layer was prepared.
[0092] 4. Dissolve 0.5 mg of 3-aminopropyl phosphate diiodate in 1 mL of ethanol to obtain a 3-aminopropyl phosphate diiodate precursor solution. Dissolve 0.5 mg of 1,4-phenyldiphosphonic acid in 1 mL of ethanol to obtain a 1,4-phenyldiphosphonic acid precursor solution. Mix the 3-aminopropyl phosphate diiodate precursor solution, 1,4-phenyldiphosphonic acid precursor solution, and ethanol in a volume ratio of 1:0:9 to obtain a solution for passivating the buried interface.
[0093] 5. Take the passivation solution obtained in step 4 and spin-coat it onto the hole transport layer obtained in step 3. The spin-coating speed is 4000 rpm / min and the spin-coating time is 30 s. Then anneal it at 100℃ for 10 min in a nitrogen atmosphere.
[0094] 6. Dissolve 571.65 mg lead iodide, 215.89 mg lead bromide, 13.35 mg lead chloride, 215.89 mg formamidinium hydroiodide, 91.45 mg cesium iodide and 14.04 mg methylammonium hydrochloride in a mixed solution of dimethylformamide and N-methylpyrrolidone in a volume ratio of 800 μL:200 μL. Stir under nitrogen atmosphere until completely dissolved to obtain perovskite precursor solution;
[0095] 7. Take the perovskite solution obtained in step 6 and coat it onto the buried interface layer obtained in step 5. The coating speed is 9 mm / s and the blade spacing is 200 μm. Dry the film by nitrogen extraction. Then anneal it in nitrogen at 130 °C for 30 min. A perovskite light-absorbing layer with a thickness of about 600 nm is prepared.
[0096] 8. Take 20 mg PC 61 BM was dissolved in 1 mL of chlorobenzene and stirred until completely dissolved to obtain PC. 61 BM solution: Dissolve 0.5 mg BCP in 1 mL isopropanol and stir until completely dissolved to obtain a buffer solution;
[0097] 9. The solution obtained in step 8 is spin-coated onto the perovskite light-absorbing layer obtained in step 7 using a spin-coating method. 61 The spin coating speed of BM was 2000 rpm / min and the spin coating time was 30 s. The spin coating speed of BCP was 5000 rpm / min and the spin coating time was 30 s to prepare the electron transport layer.
[0098] 10. A silver film with a thickness of 80 nm is deposited on the thin film obtained in step 9 to obtain a perovskite solar cell.
[0099] Experimental Results: Performance testing of solar cells was conducted, such as... Figure 5 As shown, at AM1.5, 100 mW / cm 2Under standard light intensity irradiation, the solar cell prepared in this embodiment exhibits an open-circuit voltage of 1.243 V and a short-circuit current density of 20.97 mA / cm². 2 The fill factor is 83.98%, and the efficiency is 21.93%.
[0100] Example 5
[0101] This invention provides a method for preparing a perovskite solar cell based on the synergistic passivation of the buried interface by 3-aminopropyl phosphate diiodate and 1,4-phenylbisphosphonic acid, comprising the following steps:
[0102] 1. Place an ITO conductive glass substrate (2 × 2 cm) 2 The substrate was ultrasonically cleaned sequentially with detergent, deionized water and isopropanol for 30 min, dried with nitrogen, and treated with ultraviolet ozone for 20 min to obtain a clean and well wettable ITO conductive glass substrate.
[0103] 2. Add 20 mg NiO X NiO was prepared by dissolving the powder in 1 mL of deionized water. X Hole transport layer solution;
[0104] 3. Take the NiO from step 2 X The hole transport layer solution was spin-coated onto the ITO conductive glass substrate of step 1 at a speed of 2000 rpm / min for 30 s; then, it was annealed in ambient air at 130°C for 20 min; thus, the hole transport layer was prepared.
[0105] 4. Dissolve 0.5 mg of 3-aminopropyl phosphate diiodate in 1 mL of ethanol to obtain a 3-aminopropyl phosphate diiodate precursor solution. Dissolve 0.5 mg of 1,4-phenyldiphosphonic acid in 1 mL of ethanol to obtain a 1,4-phenyldiphosphonic acid precursor solution. Mix the 3-aminopropyl phosphate diiodate precursor solution, 1,4-phenyldiphosphonic acid precursor solution, and ethanol in a volume ratio of 0:1:9 to obtain a solution for passivating the buried interface.
[0106] 5. Take the passivation solution obtained in step 4 and spin-coat it onto the hole transport layer obtained in step 3. The spin-coating speed is 4000 rpm / min and the spin-coating time is 30 s. Then anneal it at 100℃ for 10 min in a nitrogen atmosphere.
[0107] 6. Dissolve 571.65 mg lead iodide, 215.89 mg lead bromide, 13.35 mg lead chloride, 215.89 mg formamidinium hydroiodide, 91.45 mg cesium iodide and 14.04 mg methylammonium hydrochloride in a mixed solution of dimethylformamide and N-methylpyrrolidone in a volume ratio of 800 μL:200 μL. Stir under nitrogen atmosphere until completely dissolved to obtain perovskite precursor solution;
[0108] 7. Take the perovskite solution obtained in step 6 and coat it onto the buried interface layer obtained in step 5. The coating speed is 9 mm / s and the blade spacing is 200 μm. Dry the film by nitrogen extraction. Then anneal it in nitrogen at 130 °C for 30 min. A perovskite light-absorbing layer with a thickness of about 600 nm is prepared.
[0109] 8. Take 20 mg PC 61 BM was dissolved in 1 mL of chlorobenzene and stirred until completely dissolved to obtain PC. 61 BM solution: Dissolve 0.5 mg BCP in 1 mL isopropanol and stir until completely dissolved to obtain a buffer solution;
[0110] 9. The solution obtained in step 8 is spin-coated onto the perovskite light-absorbing layer obtained in step 7 using a spin-coating method. 61 The spin coating speed of BM was 2000 rpm / min and the spin coating time was 30 s. The spin coating speed of BCP was 5000 rpm / min and the spin coating time was 30 s to prepare the electron transport layer.
[0111] 10. A silver film with a thickness of 80 nm is deposited on the thin film obtained in step 9 to obtain a perovskite solar cell.
[0112] Experimental Results: Performance testing of solar cells was conducted, such as... Figure 6 As shown, at AM1.5, 100 mW / cm 2 Under standard light intensity irradiation, the solar cell prepared in this embodiment exhibits an open-circuit voltage of 1.232 V and a short-circuit current density of 20.88 mA / cm². 2 The fill factor is 83.62%, and the efficiency is 21.55%.
[0113] Comparative Example 1
[0114] The present invention provides a method for preparing a perovskite solar cell without the synergistic passivation of the buried interface by 3-aminopropyl phosphate diiodate and 1,4-phenylbisphosphonic acid, comprising the following steps:
[0115] 1. Place an ITO conductive glass substrate (2 × 2 cm) 2The substrate was ultrasonically cleaned sequentially with detergent, deionized water and isopropanol for 30 min, dried with nitrogen, and treated with ultraviolet ozone for 20 min to obtain a clean and well wettable ITO conductive glass substrate.
[0116] 2. Add 20 mg NiO X NiO was prepared by dissolving the powder in 1 mL of deionized water. X Hole transport layer solution;
[0117] 3. Take the NiO from step 2 X The hole transport layer solution was spin-coated onto the ITO conductive glass substrate of step 1 at a speed of 2000 rpm / min for 30 s; then, it was annealed in ambient air at 130°C for 20 min; thus, the hole transport layer was prepared.
[0118] 4. Dissolve 571.65 mg lead iodide, 215.89 mg lead bromide, 13.35 mg lead chloride, 215.89 mg formamidinium hydroiodide, 91.45 mg cesium iodide and 14.04 mg methylammonium hydrochloride in a mixed solution of dimethylformamide and N-methylpyrrolidone in a volume ratio of 800 μL:200 μL. Stir under nitrogen atmosphere until completely dissolved to obtain perovskite precursor solution;
[0119] 5. The perovskite solution obtained in step 4 is coated onto the hole transport layer obtained in step 3 at a coating speed of 9 mm / s and a blade spacing of 200 μm. The film is dried by nitrogen extraction. Then, it is annealed in nitrogen at 130 °C for 30 min to prepare a perovskite light-absorbing layer with a thickness of about 600 nm.
[0120] 6. Take 20 mg PC 61 BM was dissolved in 1 mL of chlorobenzene and stirred until completely dissolved to obtain PC. 61 BM solution: Dissolve 0.5 mg BCP in 1 mL isopropanol and stir until completely dissolved to obtain a buffer solution;
[0121] 7. Spin-coating the solution obtained in step 6 onto the perovskite light-absorbing layer obtained in step 5 using a spin-coating method. PC 61 The spin coating speed of BM was 2000 rpm / min and the spin coating time was 30 s. The spin coating speed of BCP was 5000 rpm / min and the spin coating time was 30 s to prepare the electron transport layer.
[0122] 8. A silver film with a thickness of 80 nm is deposited on the thin film obtained in step 7 to obtain a perovskite solar cell.
[0123] Experimental Results: Performance testing of solar cells was conducted, such as... Figure 7As shown, at AM1.5, 100 mW / cm 2 Under standard light intensity irradiation, the solar cell prepared in this embodiment exhibits an open-circuit voltage of 1.226 V and a short-circuit current density of 20.58 mA / cm². 2 The fill factor is 82.11%, and the efficiency is 20.76%.
[0124] Example 6
[0125] Unlike Examples 1-5, the substrate in this example is any one of FTO conductive glass, transparent conductive flexible plastic, crystalline silicon substrate, and copper indium gallium selenide substrate.
[0126] Example 7
[0127] Unlike Examples 1-6, the hole transport layer in this example is any one of 2PACZ, SAMs, PTAA, P3HT, and P3CT.
[0128] Example 8
[0129] Unlike Examples 1-7, the electron transport layer in this example is C. 60 .
[0130] Example 9
[0131] Unlike Examples 1-8, the buffer layer in this example is either ZnO or TPBi.
[0132] Example 10
[0133] Unlike Examples 1-9, the metal electrode material in this example is either Au or Cu.
[0134] Example 11
[0135] Unlike Examples 1-10, the solvent for the perovskite precursor solution in this example is any one or a mixture of two of γ-butyrolactone and dimethyl sulfoxide.
[0136] Example 12
[0137] Unlike Examples 1-11, the spin coating speed in this example is 1000 rpm / min and the time is 150 s.
[0138] Example 13
[0139] Unlike Examples 1-12, the annealing conditions in this example are 100°C in air for 30 minutes.
[0140] Example 14
[0141] Unlike Examples 1-13, the annealing conditions in this example are 130°C in air for 10 minutes.
[0142] In summary, a perovskite solar cell buried interface layer based on the synergistic passivation of the buried interface by 3-aminopropyl phosphate diiodate and 1,4-phenylenediamine, and its preparation method, are presented. The synergistic effect of these two molecules improves the quality of the buried interface of the perovskite film. Comparison of Examples 1-5 with comparative examples shows that the two molecules synergistically provide nucleation sites for the crystallization of the perovskite film and play a role in regulating nucleation kinetics in the early stages of perovskite film growth, thus assisting perovskite crystallization and improving film quality. The synergistic effect not only achieves bidirectional defect repair from the bottom transport layer to the top perovskite layer but also significantly reduces non-radiative recombination loss at the buried interface. Furthermore, this composite passivation layer improves the wettability of the hole transport layer surface, exhibiting excellent film uniformity, thereby significantly enhancing the operational stability of the cell while improving the photoelectric conversion efficiency. Under the same conditions, the open-circuit voltage of the solar cells prepared in Examples 1-5 is 1.232 V-1.243 V, and the short-circuit current density is 20.82 mA / cm². 2 -21.31 mA / cm 2 The fill factor was 83.21%-84.45%, and the efficiency was 21.37-22.39%. In contrast, the comparative solar cell had an open-circuit voltage of 1.226 V and a short-circuit current density of 20.58 mA / cm². 2 The fill factor is 82.11%, and the efficiency is 20.76%. The invention is effective.
[0143] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A buried interface passivation layer for perovskite solar cells based on the synergistic passivation of 3-aminopropyl phosphate diiodate and 1,4-phenylenediamine, characterized in that, The passivation material of the buried interface passivation layer is 3-aminopropylphosphonic acid hydroiodate and 1,4-phenylbisphosphonic acid, with the following structural formula: a) 3-Aminopropylphosphonate hydroiodide b) 1,4-Benzodiphosphonic acid The ratio of 3-aminopropyl phosphate hydroiodate to 1,4-benzenediphosphonic acid is x:1-x, where 0≤x≤1.
2. The method for preparing the buried interface passivation layer of the perovskite solar cell based on the synergistic passivation of 3-aminopropyl phosphate diiodate and 1,4-phenylenediamine as described in claim 1, characterized in that, 3-Aminopropyl phosphate diiodate and 1,4-phenylbisphosphonic acid were dissolved in solvents to obtain precursor solutions; the obtained precursor solutions were mixed to obtain a buried interface passivation solution; the obtained buried interface passivation solution was deposited on the hole transport layer. The precursor solution concentration is 0.01 mg / mL to 1.0 mg / mL, and the solvent is isopropanol or ethanol. The ratio of 3-aminopropyl phosphate hydroiodate to 1,4-benzenediphosphonic acid is x:1-x, 0≤x≤1.
3. A perovskite solar cell based on the synergistic passivation of the buried interface by 3-aminopropyl phosphate diiodate and 1,4-phenylenediamine, characterized in that, It is a PIN-type structure, including a transparent conductive substrate (1), a hole transport layer (2), a buried interface passivation layer (3), a perovskite (4), an electron transport layer (5), a buffer layer (6), and an electrode (7) stacked from bottom to top. The buried interface passivation layer (3) is the buried interface passivation layer of the perovskite battery based on the synergistic passivation of 3-aminopropyl phosphate diiodate and 1,4-phenylenediamine as described in claim 1 or 2.
4. A perovskite solar cell based on the synergistic passivation of the buried interface by 3-aminopropyl phosphate diiodate and 1,4-phenylenediamine as described in claim 3, characterized in that, The transparent conductive substrate (1) is selected from one of ITO conductive glass, transparent conductive flexible plastic, crystalline silicon substrate, copper indium gallium selenide substrate, and conductive flexible stainless steel.
5. A perovskite solar cell based on the synergistic passivation of the buried interface by 3-aminopropyl phosphate diiodate and 1,4-phenylenediamine according to claim 3, characterized in that, The hole transport layer (2) is made of NiO. X One of PTAA, P3CT, and SAM.
6. A perovskite solar cell based on the synergistic passivation of the buried interface by 3-aminopropyl phosphate diiodate and 1,4-phenylenediamine according to claim 3, characterized in that, The perovskite light-absorbing layer (4) simultaneously satisfies the following conditions: a) The perovskite light-absorbing layer (4) is an ABX3 type perovskite film, 0≤x≤3; wherein the A site is methylamine (MA + ), formamidin (FA) + ), Cs + and its mixed cations, with Pb at the B site. 2+ Sn 2+ and its mixed cations, with Cl at the X position. - ,Br - I - and its mixed anions; b) The thickness of the perovskite light-absorbing layer (4) is 200nm-1000nm.
7. A perovskite solar cell based on the synergistic passivation of the buried interface by 3-aminopropyl phosphate diiodate and 1,4-phenylenediamine as described in claim 3, characterized in that, The material of the electron transport layer (5) is selected from PCBM, C 60 One of SnO2.
8. A perovskite solar cell based on the synergistic passivation of the buried interface by 3-aminopropyl phosphate diiodate and 1,4-phenylenediamine as described in claim 3, characterized in that... The buffer layer (6) is any one of BCP, ZnO, or TPBi.
9. A perovskite solar cell based on the synergistic passivation of the buried interface by 3-aminopropyl phosphate diiodate and 1,4-phenylenediamine as described in claim 3, characterized in that, The electrode (7) simultaneously satisfies the following conditions: a) The electrode (7) is a metal electrode prepared by a thermal evaporation process; b) The thickness of the electrode (7) is 10nm-300nm.
10. The application of the buried interface passivation layer according to claim 1 or 2, characterized in that, Suitable for perovskite-based tandem solar cells, including at least the following structural components: a) Perovskite / perovskite tandem solar cells; b) Perovskite / crystalline silicon tandem solar cells; c) Perovskite / organic tandem solar cells; d) Perovskite / copper indium gallium selenide tandem solar cells.
Citation Information
Patent Citations
Movable platform for storing cargo and motor vehicles
PT100140A
formulations that contain steroids
PT100150A